Sistematización del proyecto de intervención socio-educativo para la prevención de la violencia contra la infancia :Experiencia con los niños, niñas. Padres y madres de familia del centro educativo intercultural bilingüe 30 de Octubre de la comunidad Santa Marianita de Pingulmí, cantón Cayambe - Estrella Torres, Washington Eduardo (2015)
Violence against children is a social problem that has always existed in all social classes and ethnic groups. The children are victims, especially within households by their parents and by people living under the same roof and tobe part of this family group become bullies or silent accomplices of different forms of violence , as are physical , psychological , sexual, neglect and negligence, all these types of violence are being harmful in children , causing serious problems in their development, growth and socialization and they can be come in trauma, feelings of inferiority, rejection, insecurity, low self-esteem, depression, anxiety, aggressive behavior and isolation. This thesis evidences the different forms of violence, causes and consequences , this being a reality where children are most vulnerable. An analysis workshops with children, parents, in which a description and characterization of beneficiaries was performed , to determine whichperceptions of violence are , how much they know about violence, and the different forms that occur within households , this could be accomplished by the work done and the polling phase and diagnostics. These two phases are the pillar in the systematization, the project will develop through awareness, which aims to raise awareness among parents about different ways of parenting , they are developing , giving them tools and new knowledge in order to reduce the use of violence , in- family . Later working in the educational intervention with children, parents and mothers, where different topics that they managed to emphasize prevention and knowledge of the proper development of social skills were discussed. Finally, the lessons of the systematization of this experience have relation to the commitments generated by parents arises.